Rehabilitation of Toothless Conditions with Dental Implants to Improve the Nutritional Status and General Health of the Terban Village Community - Rosanto, Yosaphat Bayu; Listyarifah, Dyah; Budi Nagari, Hanni Handayani (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Terban Village is a village that has a significant number of residents who suffer from toothless conditions. This condition directly affects the village population’s nutritional status and general health. This community service aimed to rehabilitate the condition of toothlessness with dental implants to improve the nutritional status and general health of the people of Terban Village. The methods used in this community service were counseling, general health, mental and dental examinations, health utility levels, radiological examinations, and dental implant treatment for the residents. The output of this community service was a counseling session that involved 70 Terban Village residents. The DMFT index of Terban Village residents was 7.47 and was still above the WHO baseline. Five respondents were selected to undergo rehabilitation procedures with dental implants. Rehabilitation of edentulous conditions with dental implants will have a positive impact on improving the nutritional status and general health of the people of Terban Village. In addition, the general health of the population has also experienced improvements, such as reducing the number of cases of nutrition-related diseases and improving the overall quality of life.